Children’s Existential Meaning-Making of Educational Robots: A Call for Dialogue - Haglund, Liza; Aldemir, Jale (Educare, 2025)
As technological advances become increasingly integrated into children’s learning environments, this paper aims to initiate a dialogue about the place and meaning of educational robots in children’s lives. We reviewed the existing literature on robots in education and the field of philosophy for children. While the existing studies undoubtedly enrich our understanding of learners’ experiences with educational robots, they stop short of explicitly dealing with existential questions. Therefore, we recommend two avenues to study children’s existential meaning-making of educational robots: educational robots as cultural tools and educational robots as part of children’s play.